2016
DOI: 10.1080/02723638.2016.1182287
|View full text |Cite
|
Sign up to set email alerts
|

Socio-spatial segregation in China and migrants’ everyday life experiences: the case of Wenzhou

Abstract: Although internal migration is one of the most frequently discussed aspects of China's twenty-first century urbanization, much of the research in this area emphasizes megacities. This paper, however, focuses on Wenzhou, a Chinese city that served as a national model for the introduction of small-scale private enterprise in the 1990s. Through a survey of migrants living in the subdistrict of Shuangyu, a settlement dominated by manufacturing workers, this article argues that socio-spatial segregation research sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 50 publications
5
49
0
Order By: Relevance
“…We found that walking duration in general was positively associated with recreational walking and social quality (i.e., seeing other people or activities), but negatively associated with disadvantaged groups (e.g., junior college students and self-employees), in line with some findings from previous studies in China [13,24,25,30,48]. In our study, the associations are further discussed across TLS.…”
Section: Three Life Stagessupporting
confidence: 91%
See 2 more Smart Citations
“…We found that walking duration in general was positively associated with recreational walking and social quality (i.e., seeing other people or activities), but negatively associated with disadvantaged groups (e.g., junior college students and self-employees), in line with some findings from previous studies in China [13,24,25,30,48]. In our study, the associations are further discussed across TLS.…”
Section: Three Life Stagessupporting
confidence: 91%
“…This may explain why the average walking duration of young adults was the shortest in this study (mean = 2.79) compared to the other two life stages [30]. In addition, participants noted that most young adults reached the average income level (Table 1), but the disadvantaged groups had to sacrifice their leisure time to work harder and earn more money, resulting in feeling tired and being less active during their rest or recreational period, as also found in a study of immigrants and social-spatial separation in Weizhou [48]. For example, a 27-year-old participant said:…”
Section: Three Life Stagessupporting
confidence: 74%
See 1 more Smart Citation
“…This reveals that these three outlet types are more variously impacted by different socioeconomic groups. One speculation is that migrants and older people in China prefer to purchase from informal street vendors or markets due to the lower prices, compared with purchasing in supermarkets and grocery stores [15,50]. Our eld observation revealed that grocery stores often occurred inside residential buildings at an extremely short distance from home, but the price of fruit and vegetables in these amenities was much higher than when bought from street vendors or in markets, partly due to higher rental costs.…”
Section: Socioeconomic Factorsmentioning
confidence: 79%
“…Secondly, to further understand the impact of food outlets on DailyWalk among different age groups, participants were categorised into younger adults (aged [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and older adults (aged 36-59). This threshold was the same as that used in previous studies in Chinese contexts [15,50]. We then performed the multivariate logistic regression model for the two age groups.…”
Section: Methodsmentioning
confidence: 99%